2017
DOI: 10.1002/jor.23665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading disrupts osteocyte plasma membranes which initiates mechanosensation events in bone

Abstract: Osteocytes sense loading in bone, but their mechanosensation mechanisms remain poorly understood. Plasma membrane disruptions (PMD) develop with loading under physiological conditions in many cell types (e.g., myocytes, endothelial cells). These PMD foster molecular flux across cell membranes that promotes tissue adaptation, but this mechanosensation mechanism had not been explored in osteocytes. Our goal was to investigate whether PMD occur and initiate consequent mechanotransduction in osteocytes during phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 49 publications
(123 reference statements)
9
55
0
Order By: Relevance
“…ATP has been shown to act as a primary signaling molecule directing cell to cell TPMD-induced calcium waves in osteocytes 7 . It was recently reported that the production and release of extracellular vesicles rich in ATP is facilitated by intracellular calcium release in osteocytes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…ATP has been shown to act as a primary signaling molecule directing cell to cell TPMD-induced calcium waves in osteocytes 7 . It was recently reported that the production and release of extracellular vesicles rich in ATP is facilitated by intracellular calcium release in osteocytes 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that mechanicallyinduced membrane disruptions occur routinely under physiological conditions in different tissues, including muscle fibers (29), gastrointestinal tract (30), heart (31), aorta (32) and bone (7,8). Despite these injuries, cell death is minimal because cells can rapidly repair these injuries (33).…”
Section: Atp Release Due To Mechanical Injurymentioning
confidence: 99%
“…We have recently reported that physiologically-relevant mechanical loading routinely injured bone cells in vitro and in vivo, resulting in release of ATP through plasma membrane disruptions, and stimulation of calcium responses in the neighbouring cells (7). These membrane disruptions in bone cells are counteracted by rapid vesicle-mediated membrane repair (7,8), which limits ATP spillage. Thus, contrary to previous generalizations that ATP is released as a bolus proportional to mechanical stimulus (9), our data suggest that mechanically-stimulated ATP release contains dynamic information about both the extent of the injury and the rate of repair.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that fluid drag forces on the osteocyte pericellular matrix (i.e., glycocalyx) are important for osteocyte mechanotransduction, and that fiber volume fraction in the osteocyte pericellular matrix is decreased in aged as compared to younger bone (Wang et al, ), but a direct relationship between osteocyte pericellular matrix and impaired mechanosensation with aging has not yet been demonstrated. We and others have shown that transient plasma membrane disruptions (PMD) develop in osteocytes with mechanical loading both in vitro (fluid flow) and in vivo (exercise), and that these PMD initiate mechanotransduction (Hagan et al, ; Mikolajewicz, Sehayek, Wiseman, & Komarova, ; Mikolajewicz, Zimmermann, Willie, & Komarova, ; Yu et al, ), suggesting that osteocytes may use PMD to detect mechanical loads and direct the activity of remodeling cells to properly adapt the matrix as needed. The effects of aging on osteocyte PMD formation, however, have not been reported.…”
Section: Introductionmentioning
confidence: 99%